(untitled) (European Journal of Pure and Applied Mathematics, 2025)
In this study, we explore the construction of a sequence of hypergroupoids derived from a quasigroup (Latin square). We demonstrate that cyclic groups yield sequences of commutative hypergroups. Additionally, under specific conditions, we establish the formation of H_v-groups and hypergroups. Various examples are provided to illustrate and support the theoretical concepts presented in this paper, offering insights into their structure and applicability.